2021
DOI: 10.3390/nu13082871
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of 16-Week Supplementation with 5HMO-Mix in Healthy-Term Human Infants to Determine Tolerability, Safety, and Effect on Growth

Abstract: Human milk oligosaccharides (HMOs) are complex sugars that occur naturally in human breast milk and provide many beneficial functions. Most formula products lack HMOs or contain only the most abundant HMO, 2′-fucosyllactose; however, benefits of HMOs come from multiple sugars. We therefore developed a mixture of five HMOs (5HMO-Mix) mimicking the natural concentrations of the top five HMOs (5.75 g/L total, comprising 52% 2′-fucosyllactose, 13% 3-fucosyllactose, 26% lacto-N-tetraose, 4% 3′-sialyllactose, and 5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 62 publications
5
59
2
Order By: Relevance
“…Sialylated HMOs are mainly composed of 3′-sialyllactose (3′-SL), 6′-sialyllactose (6′-SL), LS-tetra-saccharide a (LSTa), LS-tetra-saccharide b (LSTb), LS-tera-saccharide c (LSTc), and disialyllacto-N-tetraose (DSLNT) ( 17 , 18 ) ( Figure 2A ), and the concentration of them is about 1,000–3,300 mg/L in the colostrum and droped to about 135–2,150 mg/L in the matured human milk ( Table 1 ). Among all sialylated HMOs, the content of sialyllactose (SL) is the highest, with an estimated concentration of 170–500 μg/mL for 6′-SL in mature breast milk ( 6 , 22 24 ). SL play important roles in neonatal gut maturation, prevention of pathogen invasion, immune regulation, and prebiotic function ( 33 ).…”
Section: The Sialylated Components In Milkmentioning
confidence: 99%
“…Sialylated HMOs are mainly composed of 3′-sialyllactose (3′-SL), 6′-sialyllactose (6′-SL), LS-tetra-saccharide a (LSTa), LS-tetra-saccharide b (LSTb), LS-tera-saccharide c (LSTc), and disialyllacto-N-tetraose (DSLNT) ( 17 , 18 ) ( Figure 2A ), and the concentration of them is about 1,000–3,300 mg/L in the colostrum and droped to about 135–2,150 mg/L in the matured human milk ( Table 1 ). Among all sialylated HMOs, the content of sialyllactose (SL) is the highest, with an estimated concentration of 170–500 μg/mL for 6′-SL in mature breast milk ( 6 , 22 24 ). SL play important roles in neonatal gut maturation, prevention of pathogen invasion, immune regulation, and prebiotic function ( 33 ).…”
Section: The Sialylated Components In Milkmentioning
confidence: 99%
“…The core set of HMOs proposed in Figure 1, composed of 2 -FL, 3-FL, 3 -SL, 6 -SL, and LNT, would encompass a majority of the benefits described above and come closer than ever before to delivering a wide portion of the protection associated with breastfeeding. Indeed, this set of HMOs has been demonstrated to be safe and well tolerated in a recent multicenter clinical trial conducted in healthy full term infants up to four months of age [16].…”
Section: Discussionmentioning
confidence: 99%
“…Only very recently have advances in the large-scale production of HMOs made fortification of infant formula feasible [11,12]. There exists a growing body of scientific literature on the safety and benefits of HMO fortification [13][14][15][16], notably 2 -fucosyllactose (2 -FL) [17][18][19][20][21], the first HMO to be widely added to commercial infant formula, which is now available from several manufacturers. Researchers have identified as many as 150 unique HMOs occurring naturally in human milk at widely varying concentrations and prevalence [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of these HMOs also shifted the developing gut microbiome toward a composition more similar to breastfed infants, and decreased medication use was reported compared to non-supplemented formula fed infants ( Berger et al., 2020 ). Very recently, a European trial involving multiple centers across different countries, reported the outcome of supplementation of 5 HMOs - 2′FL, 3FL, LNT, 3′-sialyllactose (3′SL), and 6′SL ( Parschat et al., 2021 ). Overall, the 5-HMOs blend was well-tolerated by term infants enrolled and no difference in growth rates were observed when compared to non-supplemented formula ( Parschat et al., 2021 ).…”
Section: Hmos Synthesis and Supplementationmentioning
confidence: 99%
“…Very recently, a European trial involving multiple centers across different countries, reported the outcome of supplementation of 5 HMOs - 2′FL, 3FL, LNT, 3′-sialyllactose (3′SL), and 6′SL ( Parschat et al., 2021 ). Overall, the 5-HMOs blend was well-tolerated by term infants enrolled and no difference in growth rates were observed when compared to non-supplemented formula ( Parschat et al., 2021 ).…”
Section: Hmos Synthesis and Supplementationmentioning
confidence: 99%